2022
DOI: 10.1038/s41467-021-27793-5
|View full text |Cite
|
Sign up to set email alerts
|

How palladium inhibits CO poisoning during electrocatalytic formic acid oxidation and carbon dioxide reduction

Abstract: Development of reversible and stable catalysts for the electrochemical reduction of CO2 is of great interest. Here, we elucidate the atomistic details of how a palladium electrocatalyst inhibits CO poisoning during both formic acid oxidation to carbon dioxide and carbon dioxide reduction to formic acid. We compare results obtained with a platinum single-crystal electrode modified with and without a single monolayer of palladium. We combine (high-scan-rate) cyclic voltammetry with density functional theory to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(114 citation statements)
references
References 61 publications
7
89
0
Order By: Relevance
“…(iii) Pt( 111) is more active than Pd(100) in the low overpotential region; however, interestingly, this relationship shifts at higher potentials. (iv) As an observation it is known that there is a difference for Pt and Pd with respect to the CO poisoning during FAOR 8 .The ideal FAOR catalyst on the other hand should show reversible cyclic voltammetry (CV), high activity, low onset potential and stable currents, as illustrated in Figure S2.…”
Section: Round Trip Efficiency 𝜂 Hydrogenmentioning
confidence: 97%
See 2 more Smart Citations
“…(iii) Pt( 111) is more active than Pd(100) in the low overpotential region; however, interestingly, this relationship shifts at higher potentials. (iv) As an observation it is known that there is a difference for Pt and Pd with respect to the CO poisoning during FAOR 8 .The ideal FAOR catalyst on the other hand should show reversible cyclic voltammetry (CV), high activity, low onset potential and stable currents, as illustrated in Figure S2.…”
Section: Round Trip Efficiency 𝜂 Hydrogenmentioning
confidence: 97%
“…the CO 2 reduction reaction (CO2RR). 7,8 Combining these two reactions allows for a closed carbonloop with formic acid working as a liquid energy storage media. CO2RR to formic acid and the formic acid oxidation reaction (FAOR) can be written in the form:…”
Section: Round Trip Efficiency 𝜂 Hydrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al recently elucidated the mechanism behind this CO poisoning in detail. 6 On Pd, the reaction follows a direct dehydrogenation mechanism such that it does not suffer from CO poisoning. Bifunctional Pd x Pt 1−x or combinations of Pt with Au, Cu, Sn, Pb and Bi combine a high activity with a lower susceptibility to CO poisoning.…”
Section: Direct Formic Acid Fuel Cellsmentioning
confidence: 99%
“…On Pt, the FAOR typically undergoes the two oxidation pathways in parallel [16,[22][23][24]. In contrast, on Pd, it generally follows the first pathway, being fully oxidized to CO2 [17,[25][26][27][28]. Studies on different Pd facets and overlayers have revealed that FAOR on Pd is highly active and sensitive to both the catalyst structure and the electrolyte composition [29].…”
Section: Introductionmentioning
confidence: 99%